PERANG DAN KEAMANAN DALAM TINJAUAN TEORI NEOREALISME DAN INSTITUSIONALISME - Hamka Hendra Noer (Independen, 2022)
The theory of neorealism stated that the strong and powerful will dominate and monopolize the world, whereas the insignificant will become marginalized. This concept was focused on gaining benefits rather than having a profound cooperation between countries. However, the said theory which also believed in pro-war (propaganda) has been argued by institutionalism theory. The institutionalism theory proposed that the outbreak of war may be caused by a failure in political institutions. Therefore, safety issues were more than military affairs but national security and economic relations between countries. The conspicuous objectives between those theories were that the institutionalists believed in sustainable cooperation of both parties to achieve an absolute benefit, whereas the neorealists relied on gaining advantages in cooperation. The article uses the library research and implements a qualitative-critical descriptive on the research method. Discourse analysis is carried out to prevent an overlapping data in the data analysis. In conclusion, theory of neorealism implements a domination by monopolizing power to elude a cooperation to occurred. Meanwhile, the institutionalism theory would prioritize on finding a win-win solution to resolve conflict in order to evade war.